Multisensory Dimensions Effect on Affective Attitudes, Restaurant Attachment and Positive Word of Mouth of Quick-Service Restaurants: Array - Mashao, Mmakoma Priscilla; Maziriri, Eugine Tafadzwa; Chuchu, Tinashe (Acta Universitatis Danubius. Œconomica, 2020)
The constant growth of South Africa’s quick-service restaurants, also known as the fast food outlets industry, has transformed the food industry landscape, food consumption patterns, and the intensity of industry competition. As such, it is imperative for marketers in this industry to look beyond their branding and promotional efforts in order to appeal to the modern customer and a multisensory approach has become a critical strategy for the success of all businesses, especially service businesses such as restaurants. The purpose of this study was to examine the impact of multisensory dimensions (smell, sound, sight, taste and touch) on affective consumer attitudes towards quick-service restaurants as well as restaurant attachment, and in turn positive word of mouth on the restaurants in South Africa. A quantitative research approach was utilised for this investigation and a convenience sampling procedure was embraced. Data was collected from 270 quick-service restaurant student customers within the Braamfontein Business District of Johannesburg. The data analysis was done in Statistical Package for Social Sciences (SPSS) 25 for demographic data analysis and AMOS 25 was utilised for the structural equation modelling. The tested relationships produced satisfactory results consistent with how they were hypothesised. Unequivocally, it was discovered that affective attitudes and restaurant attachment had the strongest relationship of all relationships that were tested. Implications were presented as well as proposals for further research.